"I LOVE THIS COUNTRY!”: PROSES MENTAL DALAM PIDATO-PIDATO DONALD TRUMP - Hanum Lintang Siwi Suwignyo (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2022)
Mental processes, as part of the ideational function in the metafunction of discourse, referto the search for concepts of thinking, knowledge, feelings, and desires of the speaker. Thisstudy aims to understand and explore the use and trend of using mental processes byDonald Trump in his 2016–2018 speeches. The data and data sources of this research areclauses containing mental processes in Trump's victory speech (2016), critical speeches inPhoenix (2017), and campaign speeches in Evansville Rally (2018). Data were collectedemploying a transcription study of speech texts and analyzed using the theory of FunctionalGrammar M.A.K Halliday and Systemic Functional Linguistics Suzzane Eggins and TriWiratno, which were concretized through tables and percentages. The findings show thedominance of the affective mental process, namely the most frequent mental process or thehighest frequency used by Donald Trump to show his love for the people (listeners), flag,and country.